Evaluation of Antioxidant Activity and Interaction with Radical Species Using the Vesicle Conjugated Autoxidizable Triene (VesiCAT) Assay. Issue 5 (19th March 2019) - Durand, Erwann; Zhao, Yu; Ruesgas‐Ramón, Mariana; Figueroa‐Espinoza, Maria Cruz; Lamy, Samantha; Coupland, John N.; Elias, Ryan J.; Villeneuve, Pierre
Abstract : Liposomes can be used as therapeutic vehicles and membrane models to mimic cells, therefore developing new efficient assays to assess membrane oxidation of liposomes is of great importance. Their bilayer structure serves as an interesting model to investigate the antioxidant potential of compounds, as well as drug–membrane interaction. In this context, a new and high‐throughput method called "Vesicle Conjugated Autoxidizable Triene (VesiCAT)" that is based on specific UV absorbance spectral properties of a phospholipid probe, is described. The membrane oxidation under constant free radical flux generated by azo initiators, either in membrane or in aqueous phase, offers the possibility of extracting different but complementary informations in addition to the antioxidants efficacy. Thus, the VesiCAT assay represents an excellent tool not only to evaluate antioxidant capacity of molecules or extracts, but also to gain knowledge on their membrane distribution and their interaction with hydrophilic or hydrophobic reactive oxygen species. Practical Applications : Several methods have been developed to measure antioxidant capacity of molecules or extracts. However, most of them neglect the complexity of real systems; especially how the coexisting phases may get involved in the antioxidant performance. Moreover, most of the assays use accelerated oxidation tests, and they do not consider the effect of free radicals location on the antioxidant response. The VesiCAT method is a fast and efficient testing assay, implemented with a microplate reader. In addition, the aforementioned testing defect are considered and evaluated, rendering a more reliable and accurate way to predict the antioxidant potential. Thus, the VesiCAT is worth to serve as new routine assay for large‐scale antioxidant analysis, for both academic and industrial purposes, in alternative to conventional ones. The VesiCAT assay may represent a routine test for antioxidant ranking, with additional information regarding the antioxidants distribution and the evaluation of their capacity to interact with oxidant species in different cell regions. Abstract : The VesiCAT assay may represent a routine test for antioxidant ranking, with additional information regarding the antioxidants distribution and the evaluation of their capacity to interact with oxidant species in different cell regions.